2000
DOI: 10.1002/1096-9861(20001204)428:1<20::aid-cne3>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of EP1-4 prostaglandin receptors with rat hypothalamic cell groups involved in lipopolysaccharide fever responses

Abstract: The action of prostaglandin E(2) (PGE(2)) in the preoptic area is thought to play an important role in producing fever. Pharmacologic evidence suggests that, among the four subtypes of E-series prostaglandin (EP) receptors, i.e., EP(1), EP(2), EP(3), and EP(4), the EP(1) receptor mediates fever responses. In contrast, evidence from mice with EP receptor gene deletions indicates that the EP(3) receptor is required for the initial (<1 hour) fever after intravenous (i.v.) lipopolysaccharide (LPS). To investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(87 citation statements)
references
References 50 publications
2
83
0
2
Order By: Relevance
“…Serotonin has been shown to be involved in LPS-induced anorexia in rats (17), and it is abundant in neurons originating from the midbrain dorsal raphe nucleus and projecting to the hypothalamus, including the paraventricular nucleus. A clear colocalization of c-fos and EP4 mRNA in the paraventricular nucleus and other hypothalamic nuclei has been found after LPS administration in rats (30), and inhibition of PG synthesis by administration of ketorolac abolished the IL-1␤-induced c-fos expression and increase of EP4 mRNA expression in the paraventricular nucleus (42). Taken together, these data suggest a role of EP4 receptors in LPS-and cytokine-induced phenomena, such as fever and anorexia.…”
Section: Discussionsupporting
confidence: 54%
“…Serotonin has been shown to be involved in LPS-induced anorexia in rats (17), and it is abundant in neurons originating from the midbrain dorsal raphe nucleus and projecting to the hypothalamus, including the paraventricular nucleus. A clear colocalization of c-fos and EP4 mRNA in the paraventricular nucleus and other hypothalamic nuclei has been found after LPS administration in rats (30), and inhibition of PG synthesis by administration of ketorolac abolished the IL-1␤-induced c-fos expression and increase of EP4 mRNA expression in the paraventricular nucleus (42). Taken together, these data suggest a role of EP4 receptors in LPS-and cytokine-induced phenomena, such as fever and anorexia.…”
Section: Discussionsupporting
confidence: 54%
“…Because of these multiple receptors, PGE 2 commonly has versatile and often opposing actions in many tissues and cells (reviewed in Breyer et al 2001.). In situ probing, immunohistochemistry, and c-fos expression experiments in rats have shown that the EP 1 , EP 2 , and EP 3 receptors are expressed in cerebral cortex and hippocampus (Sugimoto et al 1994;Bhattacharya et al 1998;Ek et al 2000;Nakamura et al 2000;Oka et al 2000), regions of brain affected by the diseases mentioned above. Of these, the EP 3 receptor is predominantly expressed by neurons (Sugimoto et al 1994;Dumont et al 1998;Ek et al 2000;Nakamura et al 2000), whereas the EP 1 and EP 2 receptors are expressed by glia Caggiano and Kraig 1999).…”
mentioning
confidence: 99%
“…In the brain, EPs were mostly found to be associated with neuronal and glial cells (Batshake et al, 1995;Ek et al, 2000;Nakamura et al, 2000;Oka et al, 2000;Sugimoto et al, 1993;Zhang and Rivest, 1999). However, EP2 and EP4 were but recently reported to be expressed in the endothelium, and to be induced after stroke .…”
Section: Pge2 Receptorsmentioning
confidence: 99%
“…Accordingly, the four EPs have distinct distribution patterns (Batshake et al, 1995;Ek et al, 2000;Nakamura et al, 2000;Oka et al, 2000;Sugimoto et al, 1993;Zhang and Rivest, 1999). Hence they are not restricted to the typical CNS immune-responsive regions Ericsson et al, 1994;Herkenham et al, 1998) but are also present in structures like the cerebral cortex, hippocampus, thalamus or cerebellar nuclei.…”
Section: The Bbb As An Interface For Immune Signal-transductionmentioning
confidence: 99%
See 1 more Smart Citation